Percutaneous Venous Cannulation for Minimally Invasive Cardiac Surgery: The Safest and Effective Technique Described Step-by-Step - Pozzoli, Alberto; Torre, Tiziano; Toto, Francesca; Theologou, Thomas; Ferrari, Enrico; Demertzis, Stefanos (Frontiers in Surgery, 2022)
The current cardiac surgical landscape, with the expansion of minimally invasive operations, ecmo and some interventional therapies, requires a thorough knowledge of peripheral cannulation techniques. In particular, venous cannulation may appear trivial and complication-free, but this does not reflect the reality. A venous cannulation that is not performed perfectly can lead to serious life-threatening complications in several steps. The technique we describe in detail step by step, is the current gold standard in terms of safety and efficacy: from the use of ultrasound for the ultrasound-guided puncture, to the safe advancement of the super stiff guides by means of a sentinel catheter, and concluding with the smooth insertion of the venous cannula over the stiff up to SVC. More, a list of bailout manoeuvers to solve complications has been presented along with the report of institutional clinical experience since the adoption of this technique.